Silicon Micromachining for High Performance Passive Structures at W Band. (2002) - Guillon, B.; Grenier, K.; Parra, T.; Pons, P.; Cros, D.; Blondy, P.; Graffeuil, J.; Cazaux, J. L.; Plana, R.
Abstract : This paper presents a micromachined technology allowing the realization of very high aspect ratio millimeter-wave circuits. Appropriate 3D electromagnetic simulations based on the finite element method have been implemented to design the circuits. Coplanar transmission lines featuring loss level in the 2 dB range up to 105 GHz have been realized. An original silicon micromachined cavity using the whispering gallery modes properties has been realized achieving a quality factor close to 10, 000 range at 95 GHz.